Looking into inter-organizational coordination from a cultural perspective: A study on public organizations at the subnational level in Bangladesh. Issue 1 (2nd January 2023) - Ahsan, A.H. M. Kamrul; Panday, Pranab Kumar
ABSTRACT: This paper analyses inter-organizational coordination from a cultural perspective at the sub-national level, focusing on Upazila in Bangladesh. A case-oriented qualitative study reveals that organizations with similar cultures are likely to be more successful in ensuring coordination than others who do not. The study also finds that the lack of cultural computability among different public organizations at the Upazila level has ensured coordination among them is problematic. The study also identifies several factors that create barriers to cultural compatibility. These factors include colonial legacy, different working procedures, lack of similar choices and preferences, history of the development of public organizations, inequality among public officials, societal influence on public officials, and lack of inter-organizational learning programmes.